2014
DOI: 10.1097/scs.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Large Calvarial Defects With Bone Transport Osteogenesis

Abstract: This experiment provides proof of concept for BTO for large calvarial defects in a sheep model. Distraction at a rate of 0.5 mm per day may place individuals at higher risk for premature consolidation, but distraction rates did not have significant effects on regenerate quantity or quality. Future work will include the use of curvilinear distraction devices for 3-dimensional contour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Also, Gerety et al 18 conducted almost similar study in sheep animal model without using any growth enhancement factors; the outcomes were evaluated and focused on radiological, histological, and mechanical properties of the resultant newly formed bone. They concluded that bone transport DO is a promising technique for cranioplasty that may be readily translated, and the distraction rates did not have significant effects on regenerate quantity or quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Gerety et al 18 conducted almost similar study in sheep animal model without using any growth enhancement factors; the outcomes were evaluated and focused on radiological, histological, and mechanical properties of the resultant newly formed bone. They concluded that bone transport DO is a promising technique for cranioplasty that may be readily translated, and the distraction rates did not have significant effects on regenerate quantity or quality.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that bone transport DO is a promising technique for cranioplasty that may be readily translated, and the distraction rates did not have significant effects on regenerate quantity or quality. 18…”
Section: Discussionmentioning
confidence: 99%
“…Lapin >Ø 6 59,60 Canine 20 61,62 Ovine >30 [63][64][65] Porcine >Ø 10 66,67 Bone composition similar to human 2…”
Section: ≈1158% (Cancellous) 44mentioning
confidence: 99%
“…160 congenital malformation, trauma, and neoplasia. [61][62][63][64]161 Instrumented transport osteogenesis models are reported as well as self-retaining materials that facilitate detailed magnetic resonance imaging. [61][62][63][64] Collectively, calvarial defect models in both small and large mammals are valuable models for proof-of-concept testing in non-load bearing bone.…”
Section: Flat Bonementioning
confidence: 99%
See 1 more Smart Citation